Economic evaluations of antibiotic stewardship programmes 2015–2024: a systematic review - Jasmin Huser; Tamara Dörr; Alisa Berger; Philipp Kohler; Stefan P. Kuster (Swiss Medical Weekly)
BACKGROUND: Numerous studies have demonstrated the effectiveness of Antibiotic Stewardship Programmes in reducing antibiotic resistance and healthcare costs. However, the use of different methods to assess these costs, along with the uncertainty regarding which interventions are cost-effective, hampers the comparison of results and the formulation of clear recommendations. The aim of this systematic review was to provide a comprehensive overview of the available evidence on economic evaluations of Antibiotic Stewardship Programmes and to assess their impact on healthcare costs.